Development and optimization of coffee gelato: a sensory perspective. Issue 5 (25th April 2019) - Sousa, Maísa Mancini Matioli de; Antonialli, Fabio; Pereira, Rafaela Corrêa; Ribeiro, Michele Nayara; Pires, Fabiana de Carvalho; Moreira, Suzana da Silva; Leme, Paulo Henrique Montagnana Vicente; Pereira, Rosemary Gualberto Fonseca Alvarenga
Abstract : Purpose: The purpose of this paper is to optimise and characterise the sensory aspects of gelatos flavoured with different types of coffee preparations (brewed, espresso and soluble), to select the most acceptable formulation and investigate the influence of hedonic claims on the consumer acceptance of this product. Design/methodology/approach: First, the optimal concentration of each coffee type (brewed, soluble and espresso) to be added to the gelato was determined using the just-about-right scale. Second, the acceptance and purchase intentions towards gelatos flavoured with different concentrations of each type of coffee were determined. Finally, the most acceptable concentration for each flavour was selected based on purchase intentions and three other hedonic claims (i.e. texture, flavour and overall impression). Findings: The estimated optimal concentrations of coffee (in relation to syrup) were found to be 111.09, 135.31 and 59.38 per cent for brewed, espresso and soluble coffee, respectively. Gelatos flavoured with soluble coffee were accepted more readily and associated with higher purchase intentions based on the evaluated sensory attributes (i.e. colour, taste, texture, softness and overall impression). The sensory perceptions towards these gelatos did not change significantly based on the evaluated hedonic claims ("coffee", "soluble coffee" and "gourmet coffee"). This reveals that consumers may not be influenced by specific information and/or hedonic claims in the case of coffee gelatos. Originality/value: Besides encouraging the availability of a variety of coffee products on the market, this work also supports future studies aimed at the optimization of coffee products from a sensory perspective.